OTORITAS KEILMUAN GUS IZZA SADEWA DAN MEDIA BARU (PUTRA KH. IMRON JAMIL JOMBANG) - M Ulil Abshor (Islamic Communication Journal, 2019)
The study aims to uncovered the facts behind the scientific authority that was showed by Gus Izza Sadewa (the son of KH. Imron Jamil Jombang), who was only 15 years old and was able to present a scientific identity and sufism practices that was very beneficial. The author focuses on YouTube's new media as a shaping of scientific authority in the cyberculture world. The author analyzes the content analysis of some YouTube videos about Gus Izza. The content provided is manifested in aspects of contextual sufism. According to Heidi A. Campbell, there are 4 things that influence a religion or a text ideology, namely hierarchy (value), structure, ideology, and text. The results obtained from several segments of the hierarchy or values formed in the self of Gus Izza, he has Sufism and mature scientific authority, which can be proven by giving explanations about monotheism, the most important in looking for mursyhd-teachers, faith, actualizing worship that applied in daily life. All of those have the main orientation in the virtue ethics (akhlaq al-karimah).